Improving Academic Performance of Selected Grade 11 ABM Student in General Mathematics using Handouts and Reviewer (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
General mathematics is one of the core subjects in senior high school. Some of the students have difficulty in this subject because of the lack of connection between the subject and students, self-doubt, having a low IQ or what we called being slow learners, and being inattentive and lazy to memorize formulas. This common problem will result in a low grade, and it will be difficult for the students to answer the mathematical problem. This study aimed to improve the academic performance of grade 11 Accountancy, Business, and Management students in general mathematics by motivating them to think that math is not difficult unless they are lazy and do not dare to find a way to understand it easily. The researchers used descriptive design to clearly explain the variables of the study. This study also used the Survey method where the Likert Scale is being used. It is distributed to 50 participants that were chosen by using purposive sampling. The result of this study showed that providing hand-outs and reviewers improved the academic performance of grade 11 students in general mathematic subjects in terms of the following: (1) Performance tasks –providing them a handouts and reviewers helps them easily understand mathematics lessons and perform better in class. (2) Written works and quarterly assessment –by using and reading the reviewer and handouts, the students become more knowledgeable about the subject matter and make it easier for them to answer all given written activities. This research found out that providing hand-outs and reviewers helps the students to truly understand Mathematics and helps them improve their mathematical skills. The teachers and school administrators must conduct reviews and handouts that will practice the students in enhancing their mathematical skills.
Keywords: improving, academic performances, Mathematics, handouts, reviewer